Village Council Fund - Is It a Useful Tool Towards Co-Creation of Public Services? - Mariusz DYBAL (Communications of International Proceedings, 2022)
The research aim of the paper was to check whether village council fund fulfills the concept of co-creation of public services in Poland. To achieve the goal  following research tasks has been implemented: i) to identify the legal solutions of citizens cooperation, ii) to identify characteristic of village council fund in terms of co-creation of public services, iii) to identify amount and structure of village council fund, iv) to identify difficulties in using village council fund. It has been reviled that village council fund is more and more popular (in 2022 a village council fund was established in 1501 communes while in 2009 it was 1178). According to data, during the 2010-2023 the amount of expenses performed under the village council fund has increased from 168 mln PLN to 796 mln PLN. Finally, the amount of reimbursement from the state budget of part of the expenses performed under the village council fund has increased from 44 mln PLN in 2011 to 152 mln PLN in 2023. According to the research, the village council fund is an effective platform for social activation and providing services better suited to the needs of the inhabitants. Moreover, on the basis of the above data, it should be stated that the village council fund is a certain form of co-creation of public services, as the inhabitants decide on the allocation of public funds for the implementation of public services. Nevertheless it is limited version of co-creation since residents are not involved in all parts of co-creation. Though, it seems that this form of financing public tasks will be gaining in importance due to the return from the state budget of a part of the funds spent. The research years cover mainly 2009-2023. In the paper following research methods has been used: analysis of scientific literature and normative documents, co-creation methodology, comparative analysis, statistical analysis.
Keywords: village council fund; co-creation; public services; citizens